Antiplasmodial potential of Eucalyptus obliqua leaf methanolic extract against Plasmodium vivax: An in vitro study - Zareen Shehzad (De Gruyter, 2021)
Malaria is an intraerythrocytic parasitic disease caused by the genus Plasmodium of which Plasmodium vivax and Plasmodium falciparum are the major species. The high cost and associated side effects of antimalarial drugs triggered research about medicinal plants to develop alternative and low-cost drugs with lesser side effects. Therefore, this study was designed to investigate the antiplasmodial activity of the Eucalyptus obliqua L’Hér. leaf extract against P. vivax and its phytochemicals in in vitro. The methanolic extract of E. obliqua was prepared and different concentrations of the crude extract and phytochemicals were used against P. vivax. The methanolic extract of E. obliqua showed profound antiplasmodial activity (LD50 0.084 mg/mL; 80.04%) at 0.1 mg/mL concentration after 24 h. Alkaloids, flavonoids, saponins, and tannins were found in the E. obliqua methanolic extract. Only alkaloids at the concentration (0.1 mg/mL) exhibited 60.93% inhibition of P. vivax. The methanolic extract of E. obliqua exhibits antiplasmodial activity in vitro. However, in vivo efficacy is an important aspect in the testing of medicinal plants against parasitic infections and should be evaluated in future.